Control interno y gestión de inventarios en el Hospital Santa Gema Yurimaguas 2023 - Pozo Guerra, Luis Alfredo (2024)
The purpose of this final report was to determine the relationship between internal control and inventory management at the Santa Gema Yurimaguas Hospital, 2023. In which an applied method, descriptive and correlational level was used with a non-experimental design, working with 100 workers. administrative staff, to whom a questionnaire of questions was used to collect data and information. The results showed that internal control is regular (29%), because previous control actions are sometimes subject to current regulations, issuing the corresponding report on the requested matter; and supervision of employee activities is carried out. For its part, inventory management qualifies as regular (28%), since sometimes stock verifications are carried out to verify that there are no defects; However, the issuance of referral guides is almost never fulfilled; and sometimes there are periodic reviews of product entry and exit procedures. Finally, it was determined that there is a significant relationship between internal control and inventory management corroborated by a correlation coefficient of 0.771 indicating a strong positive correlation and a significance value of 0.000.